New Media Art: Aligning Artistic Creativity And Technological Media - Soreanu Cătălin (Sciendo, 2021)
This article investigates the relationship between art and technology, pointing the constants of a process of cultural digestion which is mediated by the very sovereign technological environment - the Internet. Relying on the multiplicity and hybridization of the content formats, and also on the user involved interactivity as constructive vector-relationships, new media art and the internet art are natural consequences of the artistic practices of creative appropriation of contemporary technological media. As the complexity of the relationship between art and the technological environment becomes richer than ever, we assist to the creation of a contemporary ultra-technological culture, structurally dependent on the media and responsible for relativizing the critical positioning of the art consumer. Defining the premises of the interaction with a technologically interfaced world of art, the user (reader) of the Internet as a medium of expression is - equally - a consumer, and a producer of information (content).